Long-lived quasinormal modes and gray-body factors of black holes and wormholes in dark matter inspired Weyl gravity - B. C. Lütfüoğlu (European Physical Journal C: Particles and Fields)
Abstract We calculate quasinormal modes and gray-body factors of a massive scalar field in the background of three compact objects in the Weyl gravity: Schwarzschild-like back holes, known as Mannheim–Kazanas solution, non-Schwrazschild-like black holes and traversable wormholes found recently in (Jizba and Mudruňka in Phys Rev D 110(12):124006, 2024, https://doi.org/10.1103/PhysRevD.110.124006 , arXiv:2409.08344 [gr-qc]). We show that the spectrum of the massive field is qualitatively different from massless o ne both in the frequency and time domains. While the mass term leads to much longer lifetime of the modes, the arbitrarily long-lived modes, known as quasi-resonances, are not achieved.